Percorsi dell’etimologia (Atti del Sodalizio Glottologico Milanese, 2017)
The decisive clue for an etymology is often found by chance. This paper presents four cases which come from the author’s personal experience. KEYWORDS: Italian, etymology, lexicology, lexicography, methodology